Peningkatan Kompetensi Mahasiswa Olahraga untuk Menjadi Pelatih Profesional - Bangkit Yudho Prabowo; Ely Yuliawan; Yusradinafi Yusradinafi; Alexander Kurniawan; Anggrawan Janur Putra (Abdibaraya, 2026)
Students in the Sports Coaching Education Study Program are prospective professionals being prepared to work as sports coaches at various training levels. However, there is still a gap between students' academic competencies and workforce needs, especially in designing training programs, training periodization, evaluating athletes' physical condition, applying sports science, coaching communication, and professional ethics. This Community Service activity aims to improve sports students' competencies so that they have the knowledge and skills to support their profession as professional coaches. The method used was participatory training through material delivery, interactive discussions, case studies, training program simulations, and evaluation using pre-tests and post-tests. The activity took place on 18 June 2026 in the Universitas Jambi Hall with 39 students from the Sports Coaching Education program participating. Evaluation was conducted using a questionnaire comprising 50 multiple-choice questions based on the training material. The results showed an increase in the participants' average scores from 61.58 in the pre-test to 86.45 in the post-test, an increase of 24.87 points. The greatest improvements were seen in understanding training periodization, designing training programs, and applying sports science. Besides boosting knowledge, this activity increased active participation, motivation to learn, and students' readiness to take on roles as professional sports coaches. Thus, the training proved effective in strengthening the competencies of future coaches and can serve as a model for the sustainable development of student skills through further training, field practice, and professional mentoring